2011
DOI: 10.1039/c0lc00114g
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput single-cell quantification using simple microwell-based cell docking and programmable time-course live-cell imaging

Abstract: Extracting single-cell information during cellular responses to external signals in a high-throughput manner is an essential step for quantitative single-cell analyses. Here, we have developed a simple yet robust microfluidic platform for measuring time-course single-cell response on a large scale. Our method combines a simple microwell-based cell docking process inside a patterned microfluidic channel, with programmable time-course live-cell imaging and software-aided fluorescent image processing. The budding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 42 publications
0
61
0
Order By: Relevance
“…In each microarray, also known as ‘biochips’, thousands of reaction spots (capturing agent spots) are arrayed onto a few square centimeters. It is a remarkably versatile and useful platform, particularly when dealing with very limited sample volumes in genomics [1], proteomics [2,3,4], transcriptomics [5,6], glycomics [7,8,9], metabolomics [10], and cellomics [11] research. Partially automated dispensing systems, condition controlling systems and automated signal readouts enable sophisticated experiments to be carried out by non-specialized technicians.…”
Section: Introductionmentioning
confidence: 99%
“…In each microarray, also known as ‘biochips’, thousands of reaction spots (capturing agent spots) are arrayed onto a few square centimeters. It is a remarkably versatile and useful platform, particularly when dealing with very limited sample volumes in genomics [1], proteomics [2,3,4], transcriptomics [5,6], glycomics [7,8,9], metabolomics [10], and cellomics [11] research. Partially automated dispensing systems, condition controlling systems and automated signal readouts enable sophisticated experiments to be carried out by non-specialized technicians.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of selective hydrophobic/hydrophilic surface to control liquid flow is an efficient control method. In this case, the micro/ nanostructure roughness of the microchannel can determine the liquid flow in a predetermined path, [38][39][40][41][42] as shown in Figure 16.…”
Section: Biomedicinementioning
confidence: 99%
“…Han et al, [288] reported a novel integrated microwell-structured microfluidic device that is capable of trapping single oocytes, fertilisation and subsequent embryo culturing. The device in an array format was used to capture and hold individual oocytes during the flow-through process of oocyte Integration of cell impedance analysis into a single-cell trapping microfluidic structure HeLa Impedance [277] Handling of cells in microfluidic platform using dielectrophoresis methods S.cerevisiae and sheep red blood [278] Continuous differential impedance analysis of single cells held by a hydrodynamic cell trapping HeLa Impedance [279] Determination of hydrogen peroxide (H2O 2) in individual HepG2 cells HepG2 Fluorescence [280] Single cell quantification using microwell-based docking and programmable live cell imaging S. cerevisiae Fluorescence [281] On-chip low power piezoelectric actuated micro-sorter for deflecting single particles and cells at high-speed.…”
Section: In Vitro Fertilisationmentioning
confidence: 99%